The serotonin transporter gene and functional and pathological adaptation to environmental variation across the life span - Homberg, Judith R.; van den Hove, Daniel L.A. (Progress in neurobiology, 2012)
In analogy with the accepted view that behaviour is shaped by gene×environment (G×E) interactions, G×E studies are exponentially increasing in the field of psychiatry. Whereas research was primarily driven by the premature view that negative environmental stimuli can trigger psychopathology in those subjects that are genetically predisposed, a closer look at the available data shows that G×E interactions are much more complex than initially thought. Here, we discuss G×E studies focussing on serotonin transporter (5-HTT, SERT, SLC6A4) gene variation in humans, monkeys, and rodents. Recent studies, across species, confirm the theorized 'for-better-and-for-worse' effect of low activity serotonin transporter genotypes. In addition, while 5-HTT×E interactions were thought to take place in early life, recent evidence illustrates that these interactions are also manifested in adulthood. Therefore, we discuss data based on 5-HTT×E interactions, and propose a model in which predictive adaptive responses (PARs), as shaped by early life 5-HTT×E interactions, shape responses to environmental challenges in later life, i.e. reflecting 5-HTT×E×E interactions.